BACE1 Inhibitor MK-8931 Alters Formation but Not Stability of Dendritic Spines - Blume, Tanja; Filser, Severin; Jaworska, Anna; Blain, Jean-Francois; Koenig, Gerhard; Moschke, Katrin; Lichtenthaler, Stefan F.; Herms, Jochen (Frontiers in Aging Neuroscience, 2018)
Beta-site amyloid-precursor-protein cleaving enzyme 1 (BACE1) is the rate limiting protease in the production of the amyloid-beta peptide (Aβ), which is considered to be the causative agent in the pathogenesis of Alzheimer´s Disease (AD). Therefore, the therapeutic potential of pharmacological BACE1 inhibitors is currently tested in clinical trials for AD treatment. To ensure a positive clinical outcome it is crucial to identify and evaluate adverse effects associated with BACE1 inhibition. Preclinical studies show that chronic blockade of BACE1 activity alters synaptic functions and leads to loss of dendritic spines. However, the kinetics of spine loss have not been analyzed in detail. To assess the mechanism of synapse loss, dendritic spine dynamics of pyramidal layer V cells were monitored by in vivo two-photon microscopy in the somatosensory cortex of mice, treated with the BACE1 inhibitor MK-8931. MK-8931 treatment significantly reduced levels of Aβ40 and density of dendritic spines in the brain. However, the steady decline in dendritic spine density specifically resulted from a diminished formation of new spines and not from a loss of stable spines. Furthermore, the described effects on spine formation were transient and recovered after inhibitor withdrawal. Since MK-8931 inhibition did not completely abolish spine formation, our findings suggest that carefully dosed inhibitors might be therapeutically effective without affecting the structural integrity of excitatory synapses if given at an early disease stage.